Outcomes after coronary artery bypass graft surgery: systematic review and meta-analysis comparing bilateral versus single internal thoracic artery grafts. (25th November 2020) - Stefil, M; Gaudino, M; Benedetto, U; Gray, A; Gerry, S; Lees, B; Krzych, L; Seevanayagam, S; Taggart, D; Flather, M
Abstract: Background: Patients with diabetes and/or obesity are at higher risk of adverse outcomes following coronary artery bypass grafting (CABG). The use of bilateral internal thoracic arteries (BITA) can potentially offer survival benefit in higher risk patients compared to single internal thoracic artery (SITA) in patients undergoing CABG, but the overall evidence base for BITA has not influenced guidelines, and there are concerns over increased risk of sternal wound complications. Methods: We conducted a systematic review of the literature to identify observational studies and randomised controlled trials (RCT) comparing the efficacy (mortality) and safety (sternal wound infection) of BITA and SITA in diabetic and obese patients. Results: We identified 18 observational studies and one RCT to obtain data comparing BITA and SITA in 19, 589 diabetic patients, and two observational studies and one RCT comparing BITA and SITA in 6972 obese patients. Pooled analysis demonstrated significant mortality benefit of BITA compared to SITA in diabetic patients (risk ratio [RR] 0.79; 95% confidence interval [CI] 0.70, 0.90; Z=3.62, p=0.0003; I 2 =88%) (Figure 1a). Pooled analysis in obese patients found no significant difference in mortality rates between BITA and SITA (RR 0.73, 95% CI 0.47, 1.12; Z=1.43, p=0.15; I 2 =78%) (Figure 1b). A significantly higher rate of sternal wound complications following BITA was observed in diabetic (RR 1.53, 95% CI 1.23, 1.90; Z=3.86, p=0.0001; I 2 =4%) and obese patients (RR 2.24, 95% CI 1.63, 3.07; Z=5.00, p<0.00001; I 2 =0%). Conclusions: BITA is associated with better long-term survival in diabetic patients, but most of the supportive data comes from observational studies. The effects of BITA grafting in patients who are obese is uncertain due to low numbers. BITA is associated with higher rates of sternal wound complications than SITA in both diabetic and obese patients. Further research is needed to understand if BITA has a role in higher risk patients undergoing CABG. Funding Acknowledgement: Type of funding source: None